Effects of selected obstetric-gynaecological surgery on female urinary incontinence in pre- and postmenopausal patients - Jędrzejczyk, Sławomir; Lau, Katarzyna; Wieczorek, Marek; Kłosinski, Witold; Rutkowska, Beata; Dębowski, Marcin (Menopause Review/Przegląd Menopauzalny, 2008)
The risk factors of urinary incontinence include obesity, sex hormone deficiency, infections of the urinary tract, and constipation; but the main risk factor is obstetric-gynaecological history taking into consideration the number of vaginal deliveries, fetal weight, occurrence of instrumental or abdominal delivery, and gynaecological operations. The aim of the study was to assess the frequency of urinary incontinence after selected obstetric-gynaecological operations and to define dependence between type of urinary incontinence and kind and way of the operation among pre- and postmenopausal women. In our research we included 155 women subjected to urodynamic diagnostics between March 2007 and March 2008, aged between 33 and 81 years old. Patients with urinary incontinence after obstetric-gynaecological operations constitute 40% of the whole group. Stress urinary incontinence dominates in the group of operated and non-operated women. Abdominal and vaginal surgery predispose to stress urinary incontinence. After abdominal hysterectomy stress urinary incontinence is more common. After delivery by Caesarean section mixed urinary incontinence is more frequent. Urge urinary incontinence is more frequent after vaginal reconstructive operations than after abdominal gynaecological surgery.